Impact of Crohn's disease during pregnancy on children with attention deficit hyperactivity disorder: A review. (March 2022) - Shero, Nora; Pandeya, Dipendra Raj
Abstract: Background: Iron deficiency anemia (IDA) is a common complication of inflammatory bowel disease (IBD) in pregnant women. Although studies have shown that certain maternal autoimmune diseases are associated with attention deficit hyperactivity disorder (ADHD) in children, no studies have found a relationship specifically between and IDA in pregnant women with IBD and ADHD in their children. This review aims identify a relationship between maternal Crohn's disease (CD) with IDA and ADHD in children. Materials and methods: A review of existing literature was conducted using PubMed to search for articles on pregnant women with CD and IDA and children with ADHD. The studies included nested case-control studies, cohort studies, cross-sectional studies, case-control studies, and literature reviews published from 2012 to 2021. Results: Among 876 articles generated, 11 studies were chosen for this review. Inclusion criteria consisted of no animal studies, meta-analysis or systematic reviews followed by ADHD related topics and maternal CD and IDA. The findings show that ADHD in progeny may be attributed to maternal CD. Although no studies have shown that IDA in mothers with CD is related to ADHD in offspring, several studies have shown a positive correlation between maternal IDA and ADHD in offspring. Some studies suggest inflammation in IBD during pregnancy can inflame the central nervous system, leading to ADHD in offspring. Conclusion: IDA is a prevalent complication in CD, and inadequate iron levels are associated with neurodevelopmental problems, such as ADHD. Iron therapy for pregnant mothers diagnosed with CD is suggested to prevent ADHD in offspring. Highlights: Iron deficiency anemia in Crohn's disease during pregnancy and its impact on children with ADHD. IDA in CD in pregnant women can potentially be considered as a risk factor in the pathophysiology of ADHD in offspring. Iron deficiency is the main cause of anemia in CD. Children with ADHD tend to have a higher risk of iron deficiency. Iron is involved in the dopaminergic pathway in the central nervous system.